When shapes are more than shapes: perceptual, developmental, and neurophysiological basis for attributions of animacy and theory of mind - Torabian, Sajjad; Grossman, Emily D. (Frontiers in Psychology, 2023)
Among a variety of entities in their environment, what do humans consider alive or animate and how does this attribution of animacy promote development of more abstracted levels of mentalizing? By decontextualizing the environment of bodily features, we review how physical movements give rise to perceived animacy in Heider-Simmel style animations. We discuss the developmental course of how perceived animacy shapes our interpretation of the social world, and specifically discuss when and how children transition from perceiving actions as goal-directed to attributing behaviors to observable mental states. This transition from a teleological stance, asserting a goal-oriented interpretation to an agent's actions, to a mentalistic stance allows older children to reason about more complex actions guided by hidden beliefs. The acquisition of these more complex cognitive behaviors happens developmentally at the same time neural systems for social cognition are coming online in young children. We review perceptual, developmental, and neural evidence to identify the joint cognitive and neural developmental changes associated with when children begin to mentalize and how this ability is instantiated in the brain.